Transarterial chemoembolization in hepatocellular carcinoma treatment during the COVID-19 pandemic - Filipović, Aleksandar (Medicinski podmladak, 2023)
COVID-19 pandemic has a significant impact on the treatment of hepatocellular carcinoma as a cause of delays in diagnosing and treating patients due to the limitations in access to reference centers. The availability of human resources for the care of patients with hepatocellular carcinoma has decreased, as has the availability of hospital beds and operating rooms. On the other side morbidity and mortality related to treatment are increased in patients with cirrhosis and cancer due to their immunocompromised status and thus a higher chance of contracting a severe form of the COVID-19 disease.In order to handle such a challenging situation it became essential to revise the actual recommendations for hepatocellular carcinoma strategies during COVID-19 pandemic and adapt them to daily practice in accordance with the current legislation while respecting the principles of good clinical practice.